dragon: A New Tool for Exploring Redox Evolution Preserved in the Mineral Record - Spielman, Stephanie J.; Moore, Eli K. (Frontiers in Earth Science, 2020)
The flow of energy and elements between the geosphere and biosphere can be traced through changing redox chemistry of Earth’s surface. Deep-time trends in the mineral record, including mineral age and elemental composition, reveal a dynamic history of changing redox states and chemical speciation. We present a user-friendly exploratory network analysis platform called dragon (Deep-time Redox Analysis of the Geobiology Ontology Network) to facilitate investigation of the expanding redox chemical network preserved in the mineral record throughout Earth’s history and beyond. Given a user-indicated focal element or set of focal elements, dragon constructs interactive bipartite networks of minerals and their constituent elements over a specified range in geologic-time using information from the Mineral Evolution Database (http://rruff.info/evolution/). Written in the open-source language R as a Shiny application, dragon launches a browser-based dashboard to explore mineral evolution in deep- time. We demonstrate dragon’s utility through examining the mineral chemistry of lithium (Li) over deep-time. dragon is freely available from CRAN under a GPL-3 License, with source code and documentation hosted at https://github.com/sjspielman/dragon.